Effects of metoclopramide on the expression of metalloproteinases and interleukins in left colonic anastomoses. An experimental study - Silva,Silvana Marques e (2015)
PURPOSE : To evaluate the effects of metoclopramide on metalloproteinases (MMP) and interleukins (IL) gene expression in colonic anastomoses in rats. METHODS : Eighty rats were divided into two groups for euthanasia on the 3rd or 7th postoperative day (POD), then into two subgroups for sepsis induction or not, and then into subgroups to receive either metoclopramide or saline solution. Left colonic anastomosis were performed and then analyzed. RESULTS : On the 3rd POD, metoclopramide was associated with increased expression of MMP-1a, MMP-13, and TNF-α. On the 7th POD, the transcripts of all MMPs, TNF-α, IL-1β, IFN-γ, and IL-10 of the treated animals became negatively modulated. In the presence of sepsis, metoclopramide did not change MMPs and decreased IL-6, IL-1β, IFN-γ and IL-10 gene expression on the 3rd POD. On the 7th POD, increased expression of all MMPs, IFN-γ and IL-10 and negative modulated TNF-α and IL-6 gene expression. CONCLUSION : Administration of metoclopramide increased metalloproteinases and interleukins gene expression on the 3rd postoperative day and negatively modulated them on the 7th POD. In the presence of abdominal sepsis, metoclopramide did not change MMPs and decreased ILs gene expression on the 3rd POD. On the 7th POD, the drug increased expression of all MMPs.